Impaired exercise tolerance, mitochondrial biogenesis, and muscle fiber maintenance in miR‐133a–deficient mice. Issue 11 (25th July 2016) - Nie, Yaohui; Sato, Yoriko; Wang, Chao; Yue, Feng; Kuang, Shihuan; Gavin, Timothy P.
ABSTRACT: Exercise promotes multiple beneficial effects on muscle function, including induction of mitochondrial biogenesis. miR‐133a is a muscle‐enriched microRNA that regulates muscle development and function. The role of miR‐133a inexercise tolerance hasnotbeenfully elucidated. Inthecurrent study, mice that were deficient in miR‐133a demonstrated low maximal exercise capacity and low resting metabolic rate. Transcription of the mitochondrial biogenesis regulators peroxisome proliferator‐activated receptor‐γ coactivator 1‐α, peroxisome proliferator‐activated receptor‐γ coactivator 1‐β, nuclear respiratory factor‐1, and transcription factor A, mitochondrial were lower in miR‐133a–deficient muscle, which was consistent with lower mitochondrial mass and impaired exercise capacity. Six weeks of endurance exercise training increased the transcriptional level of miR‐133a and stimulated mitochondrial biogenesis in wild‐type mice, but failed to improve mitochondrial function in miR‐133a–deficient mice. Further mechanistic analysis showed an increase in the miR‐133a potential target, IGF‐1 receptor, alongwith hyperactivation of Akt signaling, in miR‐133a–deficient mice, which was consistent with lower transcription of the mitochondrial biogenesis regulators. These findings indicate an essential role of miR‐133a in skeletal muscle mitochondrial biogenesis, exercise tolerance, and response to exercise training.—Nie, Y., Sato, Y., Wang, C., Yue, F., Kuang, S., Gavin, T. P. Impaired exercise tolerance, mitochondrial biogenesis, and muscle fiber maintenance in miR‐133a–deficient mice. FASEB J. 30, 3745–3758 (2016) www.fasebj.org